Spatial Economics and Totalitarian Temptations: The Complex Biography of August Lösch (1906-1945) - Take, Gunnar (REGION, 2023)
Among the German spatial economists August Lösch is arguably the one who has had the biggest lasting influence on international academic literature. After his death in May 1945, a legend was created according to which he was a fierce opponent to national socialism. This was part of the attempts of his former colleagues and of the German economics community at large to disguise the extent of their own involvement and their agency in advising economic and social policies of the Nazi regime. The political context of spatial planning during the Second World War was particularly damning as it in many cases presupposed genocides on nations such as Poles and Russians and on religious groups such as Jews. It was precisely with regards to Eastern Europe that Lösch’s theoretical contributions were deemed to be particularly valuable. However, the legend of his supposed opposition contained a grain of truth as he was indeed appalled by central aspects of Nazi ideology. Yet, the ability of a totalitarian regime such as the “Third Reich” to integrate the contributions of a brilliant mind and somebody who saw himself as an independent and unpolitical scholar into its decentralized and collaborative spatial research apparatus is what makes Lösch’s biography particularly interesting and relevant today.